THE EFFECT OF ESG PERFORMANCE ON FIRM VALUE: EVIDENCE FROM INDONESIA AND MALAYSIA (2021–2024) - Meiliana Jaunanda; Yoshua Sentausa (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This study examines the impact of Environmental, Social, and Governance (ESG) performance on firm value in non-financial companies listed in Indonesia and Malaysia during the period 2021–2024. Although ESG has gained substantial global attention, empirical evidence regarding its effect on firm value remains inconclusive, particularly in emerging markets. Using panel data regression analysis on 364 firm-year observations, this research investigates the individual impact of environmental, social, and governance performance on Tobin’s Q as a proxy for firm value. ESG data are obtained from Refinitiv Eikon, while financial data are collected from annual reports and market databases. The findings reveal that governance performance significantly and positively influences firm value, supporting Signal Theory and suggesting that investors in emerging markets prioritize transparency and accountability. However, environmental and social performance show no statistically significant impact. The results indicate that ESG relevance is context-dependent and that governance mechanisms remain the most critical ESG pillar in Southeast Asian capital markets. This study contributes to the sustainability accounting literature by providing updated comparative evidence from two emerging economies and offering practical implications for corporate managers and policymakers.